Relación entre el nivel de individualismo y la comunicación horizontal en las organizaciones bogotanas internacionalizadas (2018)
The aim is to study the decision making in the organizational environment that is a relevant factor in the processes of internationalization, negotiation and fulfillment of a goal in a company. The proposed hypothesis will be tested in such a way that the impact of Colombian cultural values on the SDMPs of international organizations can be evaluated. On the other hand, the research will be supported by statistical analysis using the SPSS program for the analysis of the results. The results proved that individualism has a positive impact on the horizontal communication of internationalized Bogota companies. The above can occur because Colombia and in the case of Bogota study are places with low individualism index.